Training attentional control improves cognitive and motor task performance - Ducrocq, E.; Wilson, M.; Vine, S.; Derakshan, N. (Journal of Sport & Exercise Psychology, 2016)
Attentional control is a necessary function for the regulation of goal-directed behavior. In three experiments we investigated whether training inhibitory control using a visual search task could improve task-specific measures of attentional control and performance. In Experiment 1 results revealed that training elicited a near-transfer effect, improving performance on a cognitive (antisaccade) task assessing inhibitory control. In Experiment 2 an initial far-transfer effect of training was observed on an index of attentional control validated for tennis. The principal aim of Experiment 3 was to expand on these findings by assessing objective gaze measures of inhibitory control during the performance of a tennis task. Training improved inhibitory control and performance when pressure was elevated, confirming the mechanisms by which cognitive anxiety impacts performance. These results suggest that attentional control training can improve inhibition and reduce taskspecific distractibility with promise of transfer to more efficient sporting performance in competitive contexts.